The Gerdau Group: The Creation of a Global Competitor - Lannes, José (2014)
The Gerdau Group is today one of the largest Brazilian multinational corporations. The main objective of this study is to analyze the internationalization of this group. The hypothesis is that foreign direct investment (FDI) serves as a driver for potential business growth as well as for the diversification of activities, whose objectives include the search for markets, natural resources, efficiency, and strategic resources. The principal results confirm the hypothesis, demonstrating that new FDI and diversification were necessary when growth was limited and led to the positioning of the group as the 14th largest world steel manufacturer.